The Wheat Gene TaVQ14 Confers Salt and Drought Tolerance in Transgenic Arabidopsis thaliana Plants - Cheng, Xinran; Yao, Hui; Cheng, Zuming; Tian, Bingbing; Gao, Chang; Gao, Wei; Yan, Shengnan; Cao, Jiajia; Pan, Xu; Lu, Jie; Ma, Chuanxi; Chang, Cheng; et al. (Frontiers in Plant Science, 2022)
Wheat is one of the most widely cultivated food crops worldwide, and the safe production of wheat is essential to ensure food security. Soil salinization and drought have severely affected the yield and quality of wheat. VQ genes play important roles in abiotic stress response. This study assessed the effect of the gene TaVQ14 on drought and salt stresses resistance. Sequence analysis showed that TaVQ14 encoded a basic unstable hydrophobic protein with 262 amino acids. Subcellular localization showed that TaVQ14 was localized in the nucleus. TaVQ14 was upregulated in wheat seeds under drought and salt stress. Under NaCl and mannitol treatments, the percentage of seed germination was higher in Arabidopsis lines overexpressing TaVQ14 than in wild-type (WT) lines, whereas the germination rate was significantly lower in plants with a mutation in the atvq15 gene (a TaVQ14 homolog) than in WT controls, suggesting that TaVQ14 increases resistance to salt and drought stress in Arabidopsis seeds. Moreover, under salt and drought stress, Arabidopsis lines overexpressing TaVQ14 had higher catalase, superoxide dismutase, and proline levels and lower malondialdehyde concentrations than WT controls, suggesting that TaVQ14 improves salt and drought resistance in Arabidopsis by scavenging reactive oxygen species. Expression analysis showed that several genes responsive to salt and drought stress were upregulated in Arabidopsis plants overexpressing TaVQ14. Particularly, salt treatment increased the expression of AtCDPK2 in these plants. Moreover, salt treatment increased Ca2+ concentrations in plants overexpressing TaVQ14, suggesting that TaVQ14 enhances salt resistance in Arabidopsis seeds through calcium signaling. In summary, this study demonstrated that the heterologous expression of TaVQ14 increases the resistance of Arabidopsis seeds to salt and drought stress.